Comorbidity of Type 2 Diabetes Mellitus and Depression: Clinical Evidence and Rationale for the Exacerbation of Cardiovascular Disease - Zhu, Mengmeng; Li, Yiwen; Luo, Binyu; Cui, Jing; Liu, Yanfei; Liu, Yue (Frontiers in Cardiovascular Medicine, 2022)
Depression is a common comorbidity of type 2 diabetes mellitus (T2DM). T2DM with comorbid depression increases the risk of cardiovascular events and death. Depression and T2DM and its macrovascular complications exhibited a two-way relationship. Regarding treatment, antidepressants can affect the development of T2DM and cardiovascular events, and hypoglycemic drugs can also affect the development of depression and cardiovascular events. The combination of these two types of medications may increase the risk of the first myocardial infarction. Herein, we review the latest research progress in the exacerbation of cardiovascular disease due to T2DM with comorbid depression and provide a rationale and an outlook for the prevention and treatment of cardiovascular disease in T2DM with comorbid depression.